Implementasi Penyimpanan Data Persisten pada Docker Swarm Menggunakan Network File System (NFS) - Andreas Frederius; Mahendra Data; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Docker Swarm is a distributed system development technology for managing the Docker engine group. With Docker Swarm you can run multiple containers at the same time in the Docker engine group. In a distributed method using Docker Swarm a persistent data storage is needed. But facing Docker Swarm stores data on the container, if the container is deleted then the data will also be deleted. Therefore we need a persistent alternative storage data. Network File System (NFS) is an open protocol that can be used to share files on many computer networks and operating systems. The design of the NFS architecture on Docker Swarm uses a client-server architecture. Docker Swarm as a client and NFS as a server. NFS is able to provide persistent storage data on Docker Swarm by configuring data even if the container and machine are restarted. NFS can prepare data on Docker Swarm to retrieve data that has been stored on NFS-3 data remains persistent. The average write speed performance on NFS is 30,168 KB while the working speed of reading the average on NFS is 63,939 KB.